METODA ELEMEN HINGGA ANALISIS PELAT TEORI KIRCHHOFF DAN MINDLIN - Aji, Pujo
The determination of structure plate deflection using Kirchhoff and Mindlin theory is elaborated in this thesis. Kirchhoff theory uses three strain equations, while Mindlin theory applies five strain equations, where transversal shear strain is included. The solution for both theories is processed by finite element method, of which to build stress matrix, the minimum potensial energy is used. It is in the domain of the theory of conservative energy system, the analysis is undertaken under perfectly elastic condition where heat influx is excluded. C++ computer program is used to get the result of the analysis. Verification using SAP 2000 indicates that better result is obtained by the use of Mindlin's theory for the same mesh element.